From Myth to Reality: The Transformative Power of Online Education for Nigerian Development: Lesson for Africa - Badmus, Bidemi (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Access to education is essential for the progress of society, fostering innovation, driving economic development, and facilitating political advancement (Hanushek, E. A, & Woessmann, L. 2015).While developed nations have successfully integrated online education into their systems, developing countries, such as Nigeria, encounter significant obstacles in transitioning to e-learning due to a limited online tutors and inadequate infrastructure. This research examines secondary data to assess the effects of online education in Nigeria and across Africa. Despite an increasing acceptance of e-learning, the findings highlight considerable challenges, including a deficiency of skilled online instructors, infrastructural shortcomings, high costs of internet access, and widespread negative attitudes among students, educators, and policymakers. Furthermore, there exists a bias from employers against graduates of online programs, a lack of sufficient investment in online educational initiatives by school administrations and the Nigerian government, and a persistent risk of misinformation and miseducation. Consequently, the study advocates for investments in digital infrastructure and teacher training initiatives, shifts in attitudes towards online education, the promotion of public-private partnerships to optimize resources, expertise, and funding for online education projects, the establishment of quality assurance measures to uphold the integrity of e-learning, and the encouragement of international collaborations to share best practices, resources, and expertise in online education. These steps are vital for transforming online education into a powerful tool for development.